Peran pendidikan matematika sebagai sarana pembangun karakter bangsa - Putri, Revi Syahara Shaumi (Maliki Interdisciplinary Journal, 2024)
Children with disabilities are children with a low level of social-emotional development, thus placing children at risk or the possibility of experiencing learning difficulties, socializing and being unable to control themselves. Character education can actually be integrated into all subjects including mathematics. The change in attitudes to learning mathematics from learning mathematics manually to learning mathematics by thinking mathematically has contributed to realizing the national goal, because the purpose of learning mathematics is not only to support cognitive development but to understand mathematics. affective region. In article 3 of the National Education System Law No. 20 of 2003, which states that the mission of national education is to develop skills and form national character and civilization that are of value in order to advance the nation's life. Thus, learning mathematics can be used as a tool to help shape student character.